2015
DOI: 10.1080/10288457.2015.1080934
|View full text |Cite
|
Sign up to set email alerts
|

What Constitutes Effective Mathematics Teaching? Perceptions of Teachers

Abstract: Beliefs help shape how teachers perceive effective mathematics teaching. Providers of professional development, be they local or from other countries, need to be cognisant of such perceptions. This paper seeks to answer the question, 'What do South African teachers perceive as effective and ineffective teaching for developing conceptual understanding of mathematics?' A sample of 46 mathematics teachers was shown vignettes from eight different classrooms where the lesson dealt with some aspect of teaching fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
2
2
0
1
Order By: Relevance
“…"Teachers just teach the front of it not teaching the back, so if a pupil is able to answer the 'how' and the 'why' he or she understands the back of knowledge which is very important" Glass and Maher [28] assert that justification and sense making is more than confirming whether a solution is correct or not, it allows students to gain insight into ways of thinking about problems and may then attain higher order thinking around mathematics concepts involved. This finding was similar to Stols et al' [29] finding that enhancing students' justification skills promotes a deep understanding of concepts and relations involved. Hence, processes engaged in during problem solving should be justified so that those who might have doubts will have their doubts cleared.…”
Section: Category 3 On Guiding and Fostering Justification Skills Dur...supporting
confidence: 89%
“…"Teachers just teach the front of it not teaching the back, so if a pupil is able to answer the 'how' and the 'why' he or she understands the back of knowledge which is very important" Glass and Maher [28] assert that justification and sense making is more than confirming whether a solution is correct or not, it allows students to gain insight into ways of thinking about problems and may then attain higher order thinking around mathematics concepts involved. This finding was similar to Stols et al' [29] finding that enhancing students' justification skills promotes a deep understanding of concepts and relations involved. Hence, processes engaged in during problem solving should be justified so that those who might have doubts will have their doubts cleared.…”
Section: Category 3 On Guiding and Fostering Justification Skills Dur...supporting
confidence: 89%
“…The educator's response suggested that Mathematics educators must know the content and successfully use various communication in the classroom. This aligns with the sentiments shared by Stols et al (2015) and Ubah (2021) that Mathematics educators should use PBL in the classroom because it emphasises student-centeredness with learning activities that complement the various learning demands and their diverse home backgrounds.…”
Section: Resultssupporting
confidence: 71%
“…Such a measure was intended to avoid interfering with school lessons. Following Stols, Ono and Rogan (2015), we asked learners to comment on the illustrative sketches of solution attempts by participants involved in the master's degree research project. The first author could intervene when participants experienced impasses and did not know how to proceed and/or when they sought clarifications on illustrative sketches displayed; otherwise, learners took a leading role in the discussions of errors and misconceptions discerned from the illustrative solution attempts.…”
Section: Intervention Effortsmentioning
confidence: 99%